Implementing Microservices Architecture in Student Competition Website using Web Service Method - Nuril Hadi, Hilman; Widyayuningtias P. Listio, Syntia; Kristomoyo Kristanto, Bagus (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2024)
Effective management of a student competition website is crucial in the contemporary digital landscape, as it can support a substantial number of participants and users with optimal performance. As the competition organizer, APTISI Jawa Timur Province often use a website as the platform for spreading information regarding these competitions. Recent advancements in these competitions encompass the introduction of additional levels and categories, participant administration functionalities, payment systems, work submissions, competition webinars, and the issuance of competition certificates. The competition website development team encounters difficulties in sustaining the website's features and quality. The swift advancement of information technology demands scalable and adaptable web solutions, especially for platforms that handle dynamic and intricate capabilities like student competition websites. This paper establishes the deployment of a microservices architecture on the student competition website (lokreatif.org) utilizing web service methodologies. The major goal is to improve the system's modularity, scalability, and maintainability by breaking the application into independently deployable services. Implementing microservices architecture in student competition websites allows each key function to be implemented as an independent service. This method not only improves the efficiency of development and maintenance but also facilitates more distributed development teams.